The real and perceived influence of minority groups in Poland in the twelfth and thirteenth centuries. Issue 3 (27th May 2019) - Mühle, Eduard
ABSTRACT: Foreign immigrants have played an important part in shaping medieval Polish history from the earliest period onwards. This article addresses three aspects of this influence. First, the real and perceived influence of a foreign, German wife of a leading Piast ruler during the years 1130–50. Second, the role of foreign, Jewish mint masters ( monetarii ) and their real and perceived influence on the fiscal policies of the late twelfth and early thirteenth century. Finally, the appearance of German immigrants and their real and perceived influence on the transformations of the thirteenth century.